Hydraulic characterization of the Adamawa-Cameroon aquifer using inverse slope method. Issue 3 (9th March 2023) - Asfahani, Jamal; Aretouyap, Zakari; George, Nyakno
Abstract: Fifty vertical electrical soundings were carried out in the Adamawa region of Cameroon. The interpretation was done using inverse slope method (ISM) and curve matching methods. The aim was to employ the applicability and suitability of the ISM in deciphering the vertical electrical sounding (VES) data for groundwater and hydrogeophysical purposes in the Pan-African aquifers. The ISM can be used to interpret VES data collected with any electrodes array. The results obtained by the ISM geo-electrical interpretation correlate/agree well with the available lithological logs used in constraining the interpretation. The resistivity values obtained through this method are in the range of 20–900 Ω m with a mean of 241 Ω m and a standard deviation of 228 Ω m. The aquifer thickness is in the range of 2–90 m, with an average of 33 m and a standard deviation of 21 m. Resistivity, thickness and depth of the Pan-African aquifer in the Adamawa region, Central Africa have been determined and characterized using both the ISM and an integrated protocol of interpolation technique. The ISM can therefore be recommended for the interpretation of VES measurements in the similar Pan-African context worldwide. HIGHLIGHTS: Electrical soundings were carried out in the study area. The inverse slope method is simpler than the curve matching method. Pan-African aquifer in the Adamawa region has been characterized. The area has high and low resistivities. The thickness and depth are in line with results obtained using other methods.